1965
DOI: 10.1083/jcb.27.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the Myoepithelium of the Eccrine Sweat Glands of Man

Abstract: A B S T R A C TThe secretory coils of glutaraldehyde-osmium tetroxide-fixed and Epon-Araldite-embedded eccrine sweat glands from the palms of young men were studied with the electron microscope. The myoepithclial cells lie on the epithelial side of the basement membrane and abut other epithelial elements directly. The irregularly serrated base of the cell has dense thickenings along the plasma membranc which alternate with zones bcaring pits; the smooth apical surface lacks dense thickenings, is studded with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0
2

Year Published

1968
1968
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 34 publications
2
37
0
2
Order By: Relevance
“…There are desmosomes at the intercellular bound- aries between the secretory and myoepithelial cells as well as between two adjacent myoepithelial cells as reported by some previous authors (HIBBS, 1958;ELLIS, 1965;TANDLER, 1965;TAMARIN, 1966;KNEELAND, 1966). Hemidesmosomes may occur along the basal myoepithelial surface facing the basal lamina.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…There are desmosomes at the intercellular bound- aries between the secretory and myoepithelial cells as well as between two adjacent myoepithelial cells as reported by some previous authors (HIBBS, 1958;ELLIS, 1965;TANDLER, 1965;TAMARIN, 1966;KNEELAND, 1966). Hemidesmosomes may occur along the basal myoepithelial surface facing the basal lamina.…”
supporting
confidence: 71%
“…Most research works so far carried out on the fine structure of the myoepithelial cells of various glands have used transmission electron microscopes (TAKAHASHI, 1957(TAKAHASHI, , 1958CHIQUOINE, 1958;BARGMANN and KNOOP, 1959;HOLLMANN, 1959;HAGUENAU, 232 I. KAWABATA and K. KUROSUMI: 1959;KUROSUMI et al, 1959KUROSUMI et al, , 1960SCOTT and PEASE, 1959;LEESON, 1960;ELLIS, 1965;TANDLER, 1965;TAMARIN, 1966;KUROSUMI et al, 1968). These studies demonstrated that the myoepithelial cells rest on the inner surface (epithelial side) of the basal lamina investing the outer surface of the secretory tubules or acini.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The human sweat glands have repeatedly been studied with the electron microscope concerning both the secretory portion (HIBBS,1958;IIJIMA,1959;CHARLES, 1960;KURo-SUMI et al, 1960;MUNGER, 1961;ITo and SHIBASAKI, 1966;ELLIS, 1962ELLIS, , 1967ELLIS, , 1968BRIGGMAN et al, 1981) and the duct system (HIBBS,1958;CHARLES, 1960;MUNGER, 1961;213 HASHIMOTO et al, 1966;KUROSUMI, 1977;BRIGGMAN et al, 1981). However, only one paper by SHIBASAKI and ITO (1967) has dealt with the unique portion of the human eccrine sweat gland interposed between the secretory portion and the coiled duct, i.e., the "transitional portion."…”
Section: Dark Cells Contain Irregularlymentioning
confidence: 99%